2017
DOI: 10.21037/jtd.2017.02.34
|View full text |Cite
|
Sign up to set email alerts
|

Experiences in the management of anastomotic leakages and analysis of the factors affecting leakage healing in patients with esophagogastric junction cancer

Abstract: Background: It was reported in the literatures that the incidence of anastomotic leakage in patients with esophagogastric junction cancer decreased due to application of staplers and closure devices as well as gastric conduit technique in recent years, however, it increased slightly at our center since widely using the above devices and gastric conduit techniques from 2009. The objective of this study was to summarize our experiences in the management of anastomotic leakages and analyze the factors affecting l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The difference in values between AL rates for cervical anastomosis and thoracic anastomosis are well documented. The suggested explanations for a higher rate of cervical AL are 1) the reduced blood supply available in the cervical region, 2) high anastomotic tension in a short gastric graft, 3) lack of protective tissue with rich blood supply, 4) low protein levels, especially albumin, and 5) anemia (13). International studies have demonstrated the correlation between mortality rate and the presence of an AL, a correlation not present in our study, most likely due to the small number of patients involved.…”
Section: Resultsmentioning
confidence: 99%
“…The difference in values between AL rates for cervical anastomosis and thoracic anastomosis are well documented. The suggested explanations for a higher rate of cervical AL are 1) the reduced blood supply available in the cervical region, 2) high anastomotic tension in a short gastric graft, 3) lack of protective tissue with rich blood supply, 4) low protein levels, especially albumin, and 5) anemia (13). International studies have demonstrated the correlation between mortality rate and the presence of an AL, a correlation not present in our study, most likely due to the small number of patients involved.…”
Section: Resultsmentioning
confidence: 99%
“…Grade 4 (conduit necrosis) is diagnosed by endoscopy. The following points should be considered when diagnosing AL because diagnosis and treatment of AL differ based on the variety of the disease (21,22,25). First, AL should be confirmed and classified simultaneously (21,22).…”
Section: Definitions Classifications and Risk Factorsmentioning
confidence: 99%
“…The drainage of bile, enteric content, saliva, or air via a surgically positioned drain adjacent to the anastomosis indicates a possible AL (12,14,24). With early diagnosis and treatment of AL, a tube adjacent to the anastomotic stoma can be placed at the time of surgery (22,25,39). The methylene blue swallow test is a simple and convenient method of identification-immediate discoloration of the drain will be observed after swallowing methylene blue-and is usually used for bedside diagnosis (22,31).…”
Section: Clinical Assessment and Drain Analysismentioning
confidence: 99%
“…In general surgery, smoking significantly increases the risk of developing wound complications, including post‐laparotomy incisional hernia, or even death post elective hernia repair . In colorectal surgery, the risk of anastomotic leakage is considerably increased, and comparable negative results have also been reported following surgical excision of oesophagogastric junction cancer or after liver resection . Finally, smoking has been shown to be an independent factor for wound complications and extended length of post‐operative hospital stay following laparoscopic cholecystectomy …”
mentioning
confidence: 99%
“…5 In colorectal surgery, the risk of anastomotic leakage is considerably increased, 6 and comparable negative results have also been reported following surgical excision of oesophagogastric junction cancer or after liver resection. 7,8 Finally, smoking has been shown to be an independent factor for wound complications and extended length of post-operative hospital stay following laparoscopic cholecystectomy. 9 There is strong evidence that managing nicotine dependence, and providing perioperative smoking cessation advice and support to smokers following the 5As approach, is an effective long-term strategy, as shown by the U.S. Department of Health and Human Services.…”
mentioning
confidence: 99%